Epidemic Retinitis with Positive or Negative Weil Felix Test - a Comparative Study and Outcome with Doxycycline. (17th November 2022) - Kawali, Ankush; Mahendradas, Padmamalini; Sanjay, Srinivasan; Mohan, Ashwin; Shetty, Bhujang
ABSTRACT: Purpose: To compare clinical manifestations and disease outcomes in Epidemic Retinitis (ER) with positive or negative Weil Felix Test (WFT). Methods: Retrospective, observational, comparative study. WFT positive or negative patients formed Group 1 and 2, respectively. Patients receiving oral doxycycline monotherapy formed subgroup A and B. Duration of resolution of macular edema and retinitis was compared. Results: Novel finding of "ring retinitis" was observed equally in group 1 and 2. Complete resolution of macular edema took 41.3 days (range: 30–60 days) and 43.68 days (range: 20–105 days) ( p = .668) and retinitis lesions resolved in 34.3 days (range: 14–65 days) and 34 days (range: 12–60 days) ( p = .875) in group A and B, respectively. All (n = 14) eyes with retinitis within 1 disc diameter of fovea improved better than 20/80 except 1. Conclusion: No significant difference with respect to clinical, imaging findings and the treatment outcome was observed in WFT positive or negative cases.